2013
DOI: 10.1021/jp403983y
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Transport Properties of Pristine and Doped Single-Walled Carbon Nanotube Networks

Abstract: We use noninvasive atomic force microscopy to probe the spatial electrical conductivity of isolated junctions of pristine and nitric acid treated single-walled carbon nanotube networks (SWCNT-N). By analyzing the local IV curves of SWCNTs and bundles with various diameters, the resistance per unit length and the contact resistance of their junctions are estimated to be 3–16 kΩ/μm and 29–532 kΩ, respectively. We find that the contact resistance decreases with increasing SWCNT or bundle diameter and depends on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 35 publications
7
98
0
Order By: Relevance
“…16 Note that the Fermi energy of 0.35 eV corresponds to the hole conduction in CNTs when Au or Pd is used for electrodes. The calculated tunnel current agreed with that measured by Fuhrer et al 13 Nirmalraj et al 17 and Znidarsic et al 18 measured the junction resistances of 98 kX-2.7 MX and 29-532 kX, respectively, for SWCNTs and SWCNT bundles. The former reported that the junction resistance increased as the diameters of SWCNTs or bundles increased, while the latter reported the opposite dependence.…”
Section: Tunnel Current Between Two Cntssupporting
confidence: 87%
“…16 Note that the Fermi energy of 0.35 eV corresponds to the hole conduction in CNTs when Au or Pd is used for electrodes. The calculated tunnel current agreed with that measured by Fuhrer et al 13 Nirmalraj et al 17 and Znidarsic et al 18 measured the junction resistances of 98 kX-2.7 MX and 29-532 kX, respectively, for SWCNTs and SWCNT bundles. The former reported that the junction resistance increased as the diameters of SWCNTs or bundles increased, while the latter reported the opposite dependence.…”
Section: Tunnel Current Between Two Cntssupporting
confidence: 87%
“…This question is very important since from the general consideration it is clear that the tunneling contribution to the overall electrical resistance is dominant. This is also evidenced from the results of direct measurements of the contact resistance between the bundles of nanotubes [31]. The results of our work show that doping of nanotube films significantly reduces both the tunneling and the nanotube contributions to the resistance.…”
Section: Introductionsupporting
confidence: 74%
“…As we mentioned earlier, junction resistances seem to be lower for bundles than for individual tubes. 7 Based on the seminal work of Fuhrer et al, 6 we know that junctions between metallic tubes may exhibit resistances orders of magnitudes lower than junctions between mixed or semiconducting tubes. In a dense random network of SWCNTs, we can thus assume for the purposes of the following formulation that current conduction is dominated by metallic pathways.…”
mentioning
confidence: 99%